PERAN GURU PPKN DALAM MENJAGA EKSISTENSI NILAI-NILAI KEARIFAN LOKAL SEBAGAI KEPRIBADIAN BANGSA DI ERA DIGITAL - Nuryadi, Muhammad Hendri; Widiatmaka, Pipit; Hakim, Muhammad Lukman (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
This study aims to determine the meaning of local wisdom as the nation's personality, the problems of PPKn teachers in maintaining local wisdom, and the role of PPKn teachers in maintaining local wisdom in the digital era. This study uses a qualitative approach to the literature method. The data collection technique uses documentation and the analysis used is content analysis. The results of the study show that local wisdom that develops in Indonesia is a national personality that contains religious values, humanism, nationalism, democracy, and justice. The role of PPKn learning teachers is spearhead to and educate students to be able to maintain and care for the values of local wisdom, but teachers currently have a problem that is not yet able to adapt to the digital era so in the learning process they have not been able to take advantage of varied learning methods and learning media. digitally based. To anticipate this, teachers must be able to utilize digital technology and be able to act as facilitators, managers, learning resources, motivators, inspirations, mentors, and evaluators.